Influence of a Hypothetical Inquiry Method Towards Students' Critical Thinking Skills and Learning Outcome at Class IX SMP Negeri 1 Biromaru - Warindo, Sri Suryany; Mansyur, Jusman; Kade, Amiruddin (Universitas Tadulako, 2017)
This research aimed to influence of a hypothetical inquiry method towards students' critical thinking skills and learning outcome at class IX SMP Negeri 1 Biromaru. The research method used is quasy experiment: nonequivalent control group design. The samples of the research were Class IXA as experimental group (n=30) and Class IXB as control group (n=30) academic year 2014/2015, the samples were determined by purposive sampling technique. The independent variables in this research is a hypothetical inquiry method and conventional learning while the dependent variable is the critical thinking skills and learning outcome. Data were analyzed using descriptive statistical method t-test. It can be concluded that influence of a hypothetical inquiry method had a significant effect on students’critical thinking skills and learning outcome ability at class IX of SMP Negeri 1 Biromaru.